2021
DOI: 10.7759/cureus.17755
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Bleeding Complications in Intra-Articular Injections and Arthrocentesis in Patients on Novel Oral Anticoagulants: A Systematic Review

Abstract: Novel oral anticoagulants (NOACs) are increasingly prescribed blood-thinning medication. Surpassing Warfarin, NOACs are more favored and extensively used in paroxysmal atrial fibrillation, acute coronary syndrome, and in elderly patients. Well-known benefits of novel oral anticoagulants include predictable pharmacokinetics, pharmacodynamics, and shorter half-life. However, as with any anticoagulant, there are bleeding risks with NOACs. There is a lack of evidence and consensus on the management of novel antico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A study of 117 procedures with dagabigatran continuation reported one haemarthrosis (Guillen-Astete et al, 2017). The current study adds to this accumulating evidence of safety that continuation of DOACs is a low risk strategy with musculoskeletal procedures against the risks with interruption (Brennan et al, 2019;Kotecha et al, 2022;Tarar et al, 2021).…”
Section: Direct Oral Anticoagulantsmentioning
confidence: 79%
See 3 more Smart Citations
“…A study of 117 procedures with dagabigatran continuation reported one haemarthrosis (Guillen-Astete et al, 2017). The current study adds to this accumulating evidence of safety that continuation of DOACs is a low risk strategy with musculoskeletal procedures against the risks with interruption (Brennan et al, 2019;Kotecha et al, 2022;Tarar et al, 2021).…”
Section: Direct Oral Anticoagulantsmentioning
confidence: 79%
“…With direct oral anticoagulant (DOAC) therapy, there is much less specific safety evidence for peri‐procedural management with musculoskeletal procedures (Kotecha et al., 2022; Tarar et al., 2021). There is additional complexity in that unlike warfarin, the anticoagulant effects of DOACs cannot be easily or reliably assessed in a clinical context (Dubois et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The knee is not considered to be a “deep” joint and an AI may be performed without the need to temporarily withdraw anticoagulant treatment. 35,36 HA, in contrast to the NSAIDs, does not induce an increased risk of bleeding, and therefore VS may be considered safe in these patients. The patient must, however, be warned of the risk of a skin hematoma at the point of injection.…”
Section: Resultsmentioning
confidence: 99%